Reexistindo às vozes dos “eu’s” - Lopes, Ivon Fernandes; da Silva, Larissa Dall'Agnol; Tavares, Diogo Henrique; Ubessi, Liamara Denise; Silveira, Priscila Borges; Coimbra, Valéria Cristina Christello; Jardim, Vanda Maria da Rosa (Journal of Nursing and Health, 2018)
-